Effects of TiO2 Nanoparticles on the Overall Performance and Corrosion Protection Ability of Neat Epoxy and PDMS Modified Epoxy Coating Systems - Shafaamri, Ammar; Cheng, Chiam H.; Wonnie Ma, Iling A.; Baig, Shahid B.; Kasi, Ramesh; Subramaniam, Ramesh; Balakrishnan, Vengadaesvaran (Frontiers in Materials, 2020)
Epoxy - TiO2 nanocomposite coatings were prepared by the utilization of the solution intercalation method with the presence of the sonication process and the influence of embedding different loading ratios of TiO2 nanoparticles within neat epoxy resin was investigated. To further improve the corrosion protection performance and to fulfil the hydrophobicity of the developed coated surfaces, the epoxy polymeric resin was modified with polydimethylsiloxane (PDMS) and different loading ratio of TiO2 nanoparticles was intoduced to the modified polymeric matrix to fabricate PDMS modified epoxy nanocoposite coating sytems. All developed coating systems were characterized by means of Fourier transform infrared (FTIR) spectroscopy and differential scanning calorimetry (DSC) to investigate the chemical structure and the glass transition temperatures (Tg) of the developed coating systems, respectively. The morphology, topology, optical properties, and the wettability were also examined by field emission scanning electron microscope (FESEM), energy dispersive X-rays analyzer (EDX), atomic force microscopy (AFM), ultraviolet-visible spectroscopy (UV-vis) and contact angle measurement (CA), respectively. Moreover, the electrochemical behaviour and the barrier properties of the developed coating films were investigated via electrochemical impedance spectroscopy (EIS). The findings revealed a good curing level with higher Tg values for all developed nanaocompsoite coating systems and confirmed the efficiency of the sonication process in developed well dispersed TiO2 within the polymeric matrix. Also, the obtained results revealed the ability of certain amount of TiO2 nanoparticles in enhancing the corrosion protection performance of epoxy based coating systems. The compatibility of epoxy resin, PDMS and TiO2 nanoparticles was also confirmed by achieving the hydrophobicity and obtaining the best corrosion protection performance.